PREDIKSI LAJU EROSI PADA PENGGUNAAN LAHAN BERBEDA DI DAERAH ALIRAN SUNGAI (DAS) KAWATUNA PROPINSI SULAWESI TENGAH - A. Lanyala, Andi Aghir; Hasanah, Uswah; Ramlan, Ramlan (AGROTEKBIS, 2016)
This study aims to predict the magnitude of soil erosion rate and erosion hazard index at Kawatuna watershed in Central Sulawesi. The research will contribute information to the government in relation to land-use policies and soil conservation measures. Slope grade map, soil map and land use mapwere overlaid with ArcGIS 10.0, resulted to eleven units of land use include forest land, shrubs, paddy fields mixed farms and settlements. Erosion was occurred at all units of land use except in residential type. The field survey was conducted at seven units of land use to observe the slope length, slope, vegetation dominant, and check those units whether still have potential to practise long-term farming management. Soil sampling is done randomly on each unit of land, three samples were taken from each unit namely disturbed and un-disturbed sampling Universal Soil Loss Equation (USLE) was used to predict the soil erosion rate. The results showed the erosion that occurs at the watershed Kawatuna is classified at low to moderate level. Low erosion occurs at wetland and forest and the moderate happens at mixed garden, shrub land, and fields. The dominant factor that caused erosion in this region is ground erovisity, followed by crop management and conservation measures.Key Words: Erosion Prediction, Kawatuna Watershed, land use, USLE.